Catatan atas Masalah Aktual Perjanjian Internasional - Juwana, Hikmahanto (UI Scholars Hub, 2008)
The matter of treaty is always be interesting to discuss, especially when it somes to the question whether a state will regard a treaty which has been ratified as a part of national law that could be directly executed or not. Many opinions from various experts have been spelt out in different media. This article will discuss various aspects of treaty especially in Indonesian legal system, which was previously presented in a seminar organized by Center for International Law Studies and Ministry of Foreign Affairs overviewed certain affairs regarding implementation of treaties in Indonesia.